2007
DOI: 10.1007/s00586-007-0544-2
|View full text |Cite
|
Sign up to set email alerts
|

Spinal extra-dural metastasis from Merkel cell carcinoma: a rare cause of paraplegia

Abstract: We report a rare case of Merkel cell carcinoma with extra-dural spinal metastasis causing paraplegia. There are only four reported cases in literature. A 57-year-old lady presented with a breast lump, multiple truncal skin swellings, low back pain and rapidly progressive paraplegia. MRI showed multiple epidural soft tissue masses causing neural compression. A biopsy from the truncal skin lesion was diagnosed as Merkel cell carcinoma (MCC). Posterior decompression and tumor debulking at all three sites of neura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 25 publications
1
17
0
Order By: Relevance
“…1 MCC presenting with neurological complications is rare; 2 with only four reports 1,3-5 with spinal metastasis, with only one patient having a marked neurological deficit that required surgical decompression. 6 In that report in 2008, 6 Vijay et al suggested that there had been four prior patients. However, our detailed review of those publications reveals that one 5 was a reflective letter by a primary author on a previously reported case.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…1 MCC presenting with neurological complications is rare; 2 with only four reports 1,3-5 with spinal metastasis, with only one patient having a marked neurological deficit that required surgical decompression. 6 In that report in 2008, 6 Vijay et al suggested that there had been four prior patients. However, our detailed review of those publications reveals that one 5 was a reflective letter by a primary author on a previously reported case.…”
Section: Discussionmentioning
confidence: 97%
“…This neurological presentation is not unlike the patient in Vijay et al's report. 6 However, that patient had multilevel compressive lesions without any bony destruction suggestive of instability. The rapid incomplete neurological deficit, with associated bowel and bladder incontinence, mandates an urgent decompression of the spinal cord.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…There are only five reports of spinal metastasis from MCC in the literature1,2,3,4,5; we report the sixth case.…”
Section: Introductionmentioning
confidence: 84%